Ahli Statistik Bola Basket dalam Pengembangan Sports Science - Mu'ammal, Immanuel; Firmansyah, Muhammad; Fuddin, Muhammad Khoirul (Universitas Tribhuwana Tunggadewi Malang, 2022)
Sports science is a factor that supports the sports industry. In basketball, game statistics are part of sports science. Basketball clubs in Malang need to become more familiar with match statistics, and the number of statisticians is insufficient. This community service aims to socialize and train human resources in several Malang city basketball clubs regarding game statistics. The activity is carried out in three stages: first, socialization of game statistics; second, training on the FIBA LiveStats application, third, Simulation of real games. The result of this activity is to create and form a community of basketball statisticians in Malang. This activity's existence impacts the recognition of basketball statistics, which will enhance the development of sports science. Actual experience in the field is needed to form a competent statistician, so further training is necessary.ABSTRAKSports science adalah faktor yang mampu mendukung industri olahraga. Dalam olahraga bola basket, statistik pertandingan adalah bagian dari sport science. Klub bola basket di kota Malang belum familiar dengan statistik pertandingan dan kuantitas ahli statistik belum memadai. Pengabdian masyarakat ini bertujuan untuk mensosialisasikan dan melatih sumber daya manusia di beberapa klub basket kota Malang mengenai statistik pertandingan. Pengabdian dilakukan melalui tiga tahap: pertama, sosialisasi statistik pertandingan, kedua, pelatihan aplikasi FIBA LiveStats, ketiga, Simulasi pada pertandingan. Hasil dari kegiatan ini adalah mencetak ahli statistik bola basket dan membentuk komunitas di kota Malang. Adanya kegiatan ini berdampak pada semakin dikenalnya statistik bola basket yang akan meningkatkan perkembangan sport science. Untuk membentuk ahli statistik yang kompeten maka diperlukan pengalaman nyata di lapangan maka pelatihan lanjutan perlu dilakukan.